Conjunctival botryomycoma: A case report - Mehdi Khamaily; Joumany Brahim Salem; Imane Tarib; Sidi Dahi Mounia Bouchaar; Rachid Zerrouk; Yassine Mouzari; Fouad El Asri; Karim Reda; Abdelbarre Oubaaz (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
The fleshy telangiectatic bud or pyogenic granuloma is a tumor-like lesion that develops from chronic inflammatory situations of the conjunctiva or the eyelid. The chalazion represents one of the most frequent of these situations. We report the case of a child who presented, after a chalazion, a pyogenic granuloma, treated by surgical removal.